Depression and functional disability in stroke patients - Puji Astuti; Kusnanto; Ferra Dwi Novitasari (Journal of Public Health Research, 2020)
Background: Stroke patients often suffer from depression, a mental disorder that worsens their condition and slows down the recovery process. Depression is the leading cause of functional disability due to inability to cope with daily stressors and to function independently in their activities. The purpose of this study is to analyze the relationship between depression and functional disability levels in post-stroke patients. Design and Methods: This is an analytic observational research with a cross-sectional approach. The population in exam consisted of all 4-12 week post-stroke patient in the hospital (about 139 patients). The study focused on 104 respondents, who were selected using simple random sampling techniques. Results: The results show that 62.5% stroke patients suffered mild depressive episodes after the stroke while 58.7% experienced mild disabilities. Analysis results using the Pearson Product Moment Test obtained P=0,000. This shows there is a relationship between the level of depression and the degree of functional disability in post-stroke patients. Conclusions: It can be concluded that there is a significant relationship between the levels of post-stroke depression and the functional disability. Families are expected to provide a safe, supportive, and comfortable environment to lessen the level of depression.